Pengaruh Cash Flow, Financial Distress, Growth Opportunities terhadap Prudence Akuntansi dengan Ceo Retirement sebagai Variabel Moderasi - Luniar Aulia Rachmah; Khomsiyah Khomsiyah (Cakrawala Repositori IMWI, 2024)
The purpose of this research is to determine the effect of cash flow, financial distress, growth opportunities on accounting prudence with CEO retirement as a variable moderating. Population in this research is companies listed on the Indonesia Stock Exchange 2020-2022 in consumer goods sector. By Moderated Regression AnalysistThe result of this research showed that cash flow, financial distress, growth opportunities have effects on accounting prudence, while CEO retirement does not moderate cash flow, financial distress, growth opportunities toward accounting prudence.